Tashmîm Manhaj Ta’lîm al-Lughah al-‘Arabiyah fî Qism al-Mashrafiyah al-Islâmiyah fî Jâmi’ah STEBANK al-Islâmiyah - Khambali Khambali; Nur Ali; Sutaman Sutaman (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
The Arabic language learning curriculum in universities in Islamic Banking Study Program of STEBANK follows the institution's curriculum. The study program formulates its curriculum in addition to being based on the KKNI formulation also based on needs and environmental analysis, then from these formulations various competency standards that must be mastered will be produced in order to reflect competence of graduates according to the curriculum, the study program imposes the burden on Arabic language learning to master certain Arabic language skills that support graduate competence. The research method used is qualitative approach. The data collection technique is documentation, while the purpose of this study is to provide an overview of the use of the Arabic curriculum in the Islamic banking study program STEBANK, tertiary institution. The Arabic language curriculum in this program is designed so that students are able to master the basic elements of Arabic and are able to master the elements of Arabic skills, namely listening, speaking, reading and writing in the fields of Muamalah and Islamic Economics.